Hyperhomocysteinemia in a Patient with Moyamoya Disease. (6th May 2018) - Meena, Durga Shankar; Bohra, Gopal Krishana; Meena, Mahadev; Maheshwari, Bharat Kumar
Abstract : Moyamoya disease is a chronic progressive cerebrovascular disease characterized by bilateral occlusion or stenosis of arteries around circle of Willis. We report a case of 18-year-old female presented with recurrent episodes of headache and vertigo. On cerebral angiography, the patient was diagnosed to have moyamoya disease. On further evaluation, thrombophilia profile showed increased homocysteine level. The patient was treated conservatively with cobalamin and aspirin and advised for revascularization. According to the literature, there are few case reports of moyamoya disease with thrombotic disorders. Hence, we are reporting this interesting and rare case.